Low‐Irradiance Antimicrobial Blue Light‐Bathing Therapy for Wound Infection Control - Jie Hui; Wonjoon Moon; Pu‐Ting Dong; Carolina dos Anjos; Laisa Negri; Hao Yan; Ying Wang; Joshua Tam; Tianhong Dai; R. Rox Anderson; Jeremy Goverman; Jeffrey A. Gelfand; et al. (Advanced Science)
Abstract The prevalence of antibiotic resistance and tolerance in wound infection management poses a serious and growing health threat, necessitating the exploration of alternative approaches. Antimicrobial blue light therapy offers an appealing, non‐pharmacological solution. However, its practical application has been hindered by the requirement for high irradiance levels (50–200 mW/cm2), which particularly raises safety concerns. Here, a light‐bathing strategy is introduced that employs prolonged, continuous exposure to blue light at an irradiance range lower by more than an order of magnitude (5 mW/cm2). This method consistently applies bacteriostatic pressure, keeping wound bioburden low, all while minimizing photothermal risks. Leveraging tailor‐made, wearable light‐emitting patches, preclinical trials on rat models of wound infection are conducted, demonstrating its safety and efficacy for suppressing infections induced by methicillin‐resistant Staphylococcus aureus (S. aureus) and multidrug‐resistant Pseudomonas aeruginosa (P. aeruginosa). The results pave a new way for the application of blue light therapy in wound care.